Prevalence of environmental barriers in children and adolescents with physical disabilities: a cross-sectional study - Soares, Leilan Santos; Galvão, Élida Rayanne Viana Pinheiro; Barbosa, Isabelle Ribeiro; Ferreira, Haryelle Náryma Confessor; Cruz, Rafaela da Silva; Fechine, Carla Patricia Novaes dos Santos; Marcolino, Alinne Beserra de Lucena; Sousa, Sheva Castro Dantas de; Longo, Egmar (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Introduction. Children and adolescents with physical disabilities (PD) still do not have the same opportunities as their non-disabled peers, which may be due to environmental factors and their effect on participation. Objective: The aim of this study was to evaluate the prevalence of environmental barriers in children and adolescents with PD and their associated factors in two states of Northeastern Brazil. Method. The parents or caregivers of 71 children and adolescents aged 18 years and younger with PD were interviewed, using a sociodemographic questionnaire and the Craig Hospital Inventory of Environmental Factors (CHIEF), which assesses the frequency and extent of environmental barriers. Results. The greatest environmental barriers were for Service and Assistance. In the Service and Assistance and Physical/Structural domains, the frequency of barriers was monthly, while Attitude and Support and Policies barriers were less frequent. In all the domains, the parents reported that the problems were serious. Children and adolescents with PD who walked faced barriers more frequently than those who used a wheelchair or were carried and those living in Rio Grande do Norte had more perceived barriers in the Policies domain. Conclusion. These results lead to a reflection on the role of the environment and how each state conducts national public policies aimed at children with disabilities. This can be a step towards improving the lives of children with disabilities in Northeastern Brazil, transforming environmental barriers into environmental facilitators.